Development of molecularly imprinted polymers for the detection of human chorionic gonadotropin - Radvilė Zubrytė; Liliia Mavliutova; Yadiris García; Mark V. Sullivan; Nicholas W. Turner; Francesco Patitucci; Laura C. Polania; Verónica A. Jiménez; Robert Porter; Alice Mattsson; Börje Sellergren (Scientific Reports)
Abstract Diagnostic pregnancy tests are the most widely used immunoassays for home-based use. These tests employ the well-established lateral flow assay (LFA) technique, reminiscent of affinity chromatography relying on the dual action of two orthogonal anti-hCG antibodies. Immunoassays suffer from several drawbacks, including challenges in antibody manufacturing, suboptimal accuracy, and sensitivity to adverse storing conditions. Additionally, LFAs are typically designed for single use, as the LFA technique is non-reusable. An alternative to overcome these drawbacks is to leverage molecularly imprinted polymer (MIP) technology to generate polymer-based hCG-receptors and, subsequently, non-bioreceptor-based tests. Here, we report the development of MIP nanogels for hCG detection, exploiting epitopes and magnetic templates for high-yielding dispersed phase imprinting. The resulting nanogels were designed for orthogonal targeting of two immunogenic epitopes (SV and PQ) and were thoroughly characterized with respect to physical properties, binding affinity, specificity, and sensitivity. Molecular dynamics simulations indicated a pronounced conformational overlap between the templates and the epitopes in the native protein, supporting their suitability for templating cavities for hCG recognition. Quartz crystal microbalance (QCM)-based binding tests and kinetic interaction analysis by surface plasmon resonance (SPR) revealed nanomolar dissociation constants for the MIP nanogels and their corresponding template peptides and low uptake of lutenizing hormone (LH), structurally resembling to hCG. Receptor reusability was demonstrated in the multicycle SPR sensing mode using a low pH regeneration buffer. The results suggest the feasibility of using imprinted nanogels as a class of cost-effective, stable alternatives to natural antibodies for hCG detection. We foresee applications of these binders with respect to reusable pregnancy tests and other hCG-related disease diagnostics.